Spatial Geometry Learning in Higher Education Through Flipped Classroom with Metacognitive Scaffolding: A Mixed-Methods Study - Awi Awi; Sutamrin Sutamrin; Hisyam Ihsan; Norma Nasir; Muhammad Ammar Naufal; Muhammad Ikram (Online Learning In Educational Research (OLER), 2025)
Mathematics education students continue to struggle with the complex notion of spatial geometry. Therefore, learning approaches should incorporate strong conceptual understanding. This study examined the effectiveness of flipped classroom-based geometry learning combined with metacognitive scaffolding in developing students’ spatial ability. It also identified students’ spatial knowledge needs, types of metacognitive questions posed by the teacher, and forms of scaffolding used. A mixed-methods design was employed, consisting of an exploratory qualitative phase followed by a quasi-experimental phase. The qualitative phase explored key spatial knowledge demands and scaffolding patterns through questionnaires and interviews, while the quasi-experimental phase compared three instructional conditions: flipped classroom with metacognitive scaffolding, flipped classroom without scaffolding, and conventional instruction. Results indicated that students needed four types of spatial geometry knowledge: 3D coordinate representation, geometric transformation, spatial visualization, and angle–distance relationships. Teachers’ metacognitive questions mainly emphasized awareness of understanding, while conceptual scaffolding was more dominant than metacognitive scaffolding. Quantitatively, students in the flipped classroom with metacognitive scaffolding showed greater improvements in spatial ability. These findings suggest integrating self-directed learning and metacognitive support in geometry learning that requires advanced visualization and independent thinking.